2015
DOI: 10.1016/j.neuroscience.2015.04.062
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic inhibition shapes SAM responses in rat auditory thalamus

Abstract: Auditory thalamus (medial geniculate body [MGB]) receives ascending inhibitory GABAergic inputs from inferior colliculus (IC) and descending GABAergic projections from thalamic reticular nucleus (TRN) with both inputs postulated to play a role in shaping temporal responses. Previous studies suggested that enhanced processing of temporally rich stimuli occurs at the level of MGB, with our recent study demonstrating enhanced GABA sensitivity in MGB compared to IC. The present study used sinusoidal amplitude modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
(90 reference statements)
5
14
0
Order By: Relevance
“…Units CFs and BFs ranged between 2 and 32 kHz. Similar to studies reported by Bartlett andWang (2007, 2011) and Cai et al (2014Cai et al ( , 2015, SAM responses, based on rMTF shape across f m , conformed to previously described band-pass, high-pass, low-pass, mixed (most common) or atypical types. BMFs ranged between 8 and 512 Hz, congruent with the rMTF profile types described above.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Units CFs and BFs ranged between 2 and 32 kHz. Similar to studies reported by Bartlett andWang (2007, 2011) and Cai et al (2014Cai et al ( , 2015, SAM responses, based on rMTF shape across f m , conformed to previously described band-pass, high-pass, low-pass, mixed (most common) or atypical types. BMFs ranged between 8 and 512 Hz, congruent with the rMTF profile types described above.…”
Section: Resultssupporting
confidence: 88%
“…Anaesthesia was then maintained with i.p. injections of 100% urethane (initially 1.3 mL kg -1 , then booster doses at one-third of the initial dose; Sigma-Aldrich) (Cai et al 2014;Cai & Caspary, 2015). Rats were placed in a modified (no ear bars) stereotaxic frame in an IAC sound-attenuating booth (Industrial Acoustic Co., Inc., New York, NY, USA) with the body temperature maintained at 37 ± 0.5°C using a thermostatically controlled heating blanket.…”
Section: Anaesthetized Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neural inhibition has also been shown to be crucial for shaping neural activity elicited by amplitude-modulated sounds (Yang & Pollak, 1997;Backoff et al, 1999;Cai & Caspary, 2015; but see also Caspary et al, 2002;Zhang & Kelly, 2003). Yet, the direction in which a reduction in neural inhibition affects neural synchronisation is not clear.…”
Section: Effects Of Ageing On Response Magnitude and Neural Synchronimentioning
confidence: 99%
“…It shapes input/output functions, alters frequency tuning, and sharpens temporal response accuracy while gating neurotransmission to auditory cortex (AI) (Bartlett, 2013; Edeline, 2011; Llano et al, 2000; Richardson et al, 2012; Wang et al, 2008). In vivo and in vitro electrophysiological findings suggest distinct properties of inhibitory neurotransmission in the MGB relative to other ascending auditory structures, such as inferior colliculus (IC) (Cai et al, 2015; Cai et al, 2013; Richardson et al, 2011). The rat MGB contains relatively few GABAergic interneurons, but there are substantial GABAergic inhibitory projections from inferior colliculus and from the thalamic reticular nucleus (Bartlett et al, 2000; Peruzzi et al, 1997; Saint Marie et al, 1997b; Winer et al, 1988; Winer et al, 1996a; Winer et al, 1996b).…”
Section: 0 Gabaa Receptorsmentioning
confidence: 99%